Acute diverticulitis – Aspects of diagnostics with computed tomography imaging - Mäntymäki, Leena-Mari (fi=Turun yliopisto|en=University of Turku|, 2025)
The incidence of acute diverticulitis – common disease in Western countries – is increasing worldwide. Acute diverticulitis can be divided by its degree of severity into uncomplicated and complicated forms. Accurate diagnosis is a prerequisite for choosing optimal treatment and follow-up. Currently, the diagnosis is made using computed tomography imaging. Although the accuracy of computed tomography imaging in the diagnosis of acute diverticulitis is good, differential diagnostics can be challenging. The purpose of this dissertation was to investigate the risk of colorectal cancer after computed tomography-verified acute diverticulitis with special interest in long-term follow-up. We also aimed to assess the usefulness of reassessment of computed tomography scans and the role of experience of radiologists in emergency settings in the diagnosis of acute diverticulitis. In addition, we aimed to create a risk score for acute diverticulitis to distinguish uncomplicated and complicated forms of the disease without using computed tomography imaging by evaluating risk factors for complicated acute diverticulitis. We found that further colonic investigations were not needed after an attack of uncomplicated acute diverticulitis, as the risk of underlying colorectal cancer was low, although the risk was increased in the case of complicated disease in the short-term follow-up. No cases of colorectal cancer associated with acute diverticulitis were observed in the long-term follow-up. Reassessment of computed tomography reports in emergency settings changed the treatment or diagnosis in 5% of cases. The role of a radiologist’s experience was not statistically significant, and reports given by residents were comparable to reports given by consultants. Based on statistically significant risk factors of complicated acute diverticulitis, we created a novel risk score for acute diverticulitis that, without computed tomography imaging, accurately separated patients with a potentially severe disease from those without.

Akuutti divertikuliitti — näkökulmia tietokonetomografian käytöstä diagnostiikassa Akuutti divertikuliitti on länsimaissa yleinen sairaus, jonka ilmaantuvuus on väestön ikääntymisen myötä kasvussa. Akuutti divertikuliitti voidaan jakaa vaikeusasteen mukaan komplisoitumattomaan ja komplisoituneeseen muotoon, joiden hoitolinjat eroavat toisistaan. Optimaalisen hoidon ja jatkohoidon valinnan edellytyksenä on tarkka diagnoosi, johon käytetään yleensä tietokonetomografiakuvausta. Vaikka tietokonetomografian tarkkuus divertikuliitin diagnostiikassa on hyvä, voi erotusdiagnostiikka olla haastavaa. Tämän väitöskirjatyön tarkoituksena oli selvittää paksusuolen syövän riskiä tietokonekuvatun akuutin divertikuliitin jälkeen ja selvittää onko paksusuolen jatkotutkimuksista divertikuliitin jälkeisessä seurannassa hyötyä erityisesti pitkäaikaisseurannassa. Tutkimme myös, onko päivystysajalla tehdyn tietokonetomografia-kuvauksen kaksoisluenta hyödyllistä, sekä radiologin kokemuksen merkitystä akuutin divertikuliitin diagnostiikassa. Lisäksi selvitimme komplisoituneen akuutin divertikuliitin riskitekijöitä, joiden perusteella tavoitteemme oli luoda pisteytyssysteemi erottamaan komplisoitumaton ja komplisoitunut tautimuoto toisistaan ilman tietokonetomografiakuvausta. Akuutin, tietokonetomografialla diagnosoidun komplisoitumattoman divertikuliitiin jälkeen paksusuolen jatkotutkimuksista ei todettu olevan hyötyä, sillä syöpäriski oli hyvin matala. Komplisoituneeseen divertikulittiin sen sijaan liittyi korkeampi syöpäriski lyhyessä seurannassa. Pitkän aikavälin seurannassa ei havaittu paksusuolen syöpätapauksia akuuttiin divertikuliittiin liittyen. Päivystyspoli-klinikalla tehtyjen tietokonetomografiakuvausten kaksoisluenta muutti hoitoa tai diagnoosia 5 %:ssa tapauksia. Radiologin kokeneisuudella ei ollut merkitystä diagnoosin osuvuudessa. Tilastollisesti merkittävien komplisoituneen akuutin divertikuliitin riskitekijöiden perusteella loimme pisteytyssysteemin, joka osoittautui hyödylliseksi taudin vaikeusasteen ennustamisessa.